Chalcones with potential antibacterial and antibiofilm activities against periodontopathogenic bacteria - Satokata, Alessandra Akemi Cury (2022)
Objectives: Periodontitis is a pathology resulting from complex interaction of microorganisms in the dental biofilm with the host's immune system. Increased use of antibiotics associated with their inappropriate use has increased resistance levels in anaerobic bacteria. Therefore, identifying new antimicrobial compounds, such as chalcones, is urgent. This study evaluates the antibacterial activity and the antibiofilm activity of 15 chalcones against the periodontopathogenic bacteria Prevotella nigrescens (ATCC 33563), P. oralis (ATCC 33269), Peptostreptococcus anaerobius (ATCC 27337), Actinomyces viscosus (ATCC 43146), Porphyromonas asaccharolytica (ATCC 25260), and Fusobacterium nucleatum (ATCC 25586). Methods: The compounds were evaluated by minimum inhibitory concentration (MIC) and minimum biofilm inhibitory concentration (MBIC) tests. Results: Compounds 1–6 showed good antibacterial and antibiofilm activities against most of the evaluated bacteria: MIC was lower than or equal to 6.25 μg/mL, biofilm biomass was reduced by 95%, and the compounds at concentrations between 0.78 and 100 μg/mL totally inhibited cell viability. Among the tested chalcones, 3 stood out: it was effective against all the bacteria, as revealed by the MIC and MBIC results. Conclusions: Our results have consolidated a base for the development of new studies on the effects of the tested chalcones as agents to combat and to prevent periodontitis.